Computational Thinking Through Unplugged Programming Activities : Exploring Students’ Learning Experiences - Lim, Bih Loong (Universiti Malaysia Sarawak (UNIMAS), 2019)
In the recent year, Computational Thinking (CT) has gained much attention in educational research and practice. CT skills can be taught via computing activities that involve different types of programming tasks or via Unplugged Programming Activities (UPA) that do not involve the use of digital devices to represent and deliver programming concepts. UPA is an appropriate teaching approach for schools that do not have sufficient technological infrastructure. Studies have shown the effectiveness of UPA in developing CT skills and is comparable to the technology driven learning method. The aim of this research study is to explore the experience of primary school students’ on learning algorithm (one of the CT skills) through UPA. A total of thirty-one participants took the pre-test, followed by exposure to the UPA learning material and post-test in this study. Based on their pre-test and post-test results, nine of them were selected for individual interview. The result shows that there is no significant effect of the learning material in increasing the participants’ algorithm skill. However, the mean for post-test score is slightly higher than the mean for pre-test score. From the responses gathered through the interview sessions, four theme which are Good Learning Quality, Much Knowledge, Easy and Useful have been derived.